A microphysiological model of the human placental barrier. Issue 16 (27th May 2016) - Blundell, Cassidy; Tess, Emily R.; Schanzer, Ariana S. R.; Coutifaris, Christos; Su, Emily J.; Parry, Samuel; Huh, Dongeun
Abstract : We present a microengineered cell culture device designed to mimic the maternal–fetal interface in the human placenta. Abstract : During human pregnancy, the fetal circulation is separated from maternal blood in the placenta by two cell layers – the fetal capillary endothelium and placental trophoblast. This placental barrier plays an essential role in fetal development and health by tightly regulating the exchange of endogenous and exogenous materials between the mother and the fetus. Here we present a microengineered device that provides a novel platform to mimic the structural and functional complexity of this specialized tissue in vitro . Our model is created in a multilayered microfluidic system that enables co-culture of human trophoblast cells and human fetal endothelial cells in a physiologically relevant spatial arrangement to replicate the characteristic architecture of the human placental barrier. We have engineered this co-culture model to induce progressive fusion of trophoblast cells and to form a syncytialized epithelium that resembles the syncytiotrophoblast in vivo . Our system also allows the cultured trophoblasts to form dense microvilli under dynamic flow conditions and to reconstitute expression and physiological localization of membrane transport proteins, such as glucose transporters (GLUTs), critical to the barrier function of the placenta. To provide a proof-of-principle for using this microdevice to recapitulate native function of the placental barrier, we demonstrated physiological transport of glucose across the microengineered maternal–fetal interface. Importantly, the rate of maternal-to-fetal glucose transfer in this system closely approximated that measured in ex vivo perfused human placentas. Our "placenta-on-a-chip" platform represents an important advance in the development of new technologies to model and study the physiological complexity of the human placenta for a wide variety of applications.